2014
DOI: 10.1186/gb-2014-15-4-r58
|View full text |Cite|
|
Sign up to set email alerts
|

Repression of chimeric transcripts emanating from endogenous retrotransposons by a sequence-specific transcription factor

Abstract: BackgroundRetroviral elements are pervasively transcribed and dynamically regulated during development. While multiple histone- and DNA-modifying enzymes have broadly been associated with their global silencing, little is known about how the many diverse retroviral families are each selectively recognized.ResultsHere we show that the zinc finger protein Krüppel-like Factor 3 (KLF3) specifically silences transcription from the ORR1A0 long terminal repeat in murine fetal and adult erythroid cells. In the absence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 73 publications
0
10
1
Order By: Relevance
“…There are reports from studies in mice or human cancer cells where a LTR element gives rise to a chimeric protein by virtue of being spliced to a protein-coding gene 34,35 . In line with these reports, we show that the treatment-induced expression of LTRs generates numerous fusion-transcripts that encode novel protein isoforms, often lacking N-terminal peptide sequences important for proper protein function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are reports from studies in mice or human cancer cells where a LTR element gives rise to a chimeric protein by virtue of being spliced to a protein-coding gene 34,35 . In line with these reports, we show that the treatment-induced expression of LTRs generates numerous fusion-transcripts that encode novel protein isoforms, often lacking N-terminal peptide sequences important for proper protein function.…”
Section: Discussionmentioning
confidence: 99%
“…A T7-promoter sequence was introduced by re-amplification of the purified PCR products with the same reverse primers and forward primers harboring an extended T7-promoter sequence at the 5′-end. PCR fragments were incubated with the Quick Coupled Transcription/Translation System (Promega) in the presence of [ 35 S]-methionine.…”
Section: Methodsmentioning
confidence: 99%
“…In support of this model, a substantial number of LTRs have been reported to function as tissue-specific primary or alternative promoters in a variety of mammalian cell types, including in the early mouse embryo, placenta, human and mouse pluripotent stem cells, mouse erythroid cells and growing mouse oocytes (Buzdin et al, 2006; Cohen et al, 2009; Faulkner et al, 2009; Fort et al, 2014; Karimi et al, 2011; Macfarlan et al, 2012; Mak et al, 2014; Peaston et al, 2004; Veselovska et al, 2015a; Wolf et al, 2015b). Notably, many of the LTRs that have apparently been exapted as genic promoters are not only lineage-specific but also show clear differences in transcriptional activity between cell types in the given species.…”
Section: Introductionmentioning
confidence: 93%
“…In addition to promoting gene expression, the co-option of LTRs as promoters also provides the opportunity for TF-directed repression, as evidenced by a recent study which found that KLF3 enforces transcriptional repression of ORR1A0 LTR-driven transcripts in mouse fetal and adult erythroid cells (Mak et al, 2014). Whether suppression of such ORR1A0 LTR-driven chimeric transcripts serves only to prevent aberrant genic transcription emanating from the LTR remains to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…In the study [ 1 ] a gel depicted in Fig. 2 a was labelled in a way which suggests that the sample comes from a Klf3 −/− knockout mouse.…”
mentioning
confidence: 99%